Effects of feeding frequency on the enzymes and genes involved in oxidative stress in juvenile yellow catfish Pelteobagrus fulvidraco (Richardson) exposed to ammonia. (7th June 2017) - Fan, Xiwei; Li, Ming; Yuan, Lixia; Lai, Hang; Song, Meize; Wang, Rixin; Zheng, Rongquan
Abstract: Optimal feeding strategies improve fish growth and health but may be affected by ammonia stress in closed rearing systems such as tanks or ponds. This study aimed to evaluate the effects of feeding frequency and ammonia levels in rearing water on the enzymes and genes involved in oxidative stress of yellow catfish. Experiment (ammonia exposure) and control groups were randomly assigned to one of three feeding frequencies (1, 2 and 4 times daily) for 8 weeks. Weight gain increased as feeding frequency increased from 1 to 4 times daily, but feed conversion ratio values decreased. The highest survival in ammonia group was found when fish was fed 2 times daily. Glutathione peroxidase activity and total antioxidant capacity in liver and brain of fish exposed to ammonia increased as feeding frequency increased from 1 to 4 times daily. Liver malondialdehyde content in control group decreased as feeding frequency increased from 1 to 4 times daily. The lowest liver malondialdehyde content in ammonia group was observed when fish was fed 2 times daily. Liver mRNA expression of superoxide dismutase and catalase in control group increased as feeding frequency increased from 1 to 4 times daily, but the highest superoxide dismutase and catalase expression in ammonia group were observed when fish were fed 2 times daily. This study indicates that higher feeding frequency of yellow catfish exposed to ammonia could result in oxidative stress and poor survival. The optimal feeding frequency of yellow catfish exposed to ammonia is 2 times daily.